Phylogenetic Relationship of the Longhorn Grasshopper Ruspolia differens Serville (Orthoptera: Tettigoniidae) from Northwest Tanzania Based on 18S Ribosomal Nuclear Sequences. (21st May 2013) - Matojo, Nicodemus D.; Hosea, Keneth M.
Abstract : Previously, the biology of the longhorn grasshopper Ruspolia differens Serville (Orthoptera: Tettigoniidae) from northwest Tanzania was mainly inferred based on the morphological and behavioural characters with which its taxonomic status was delineated. The present study complements the previous analysis by examining the phylogenetic relationship of this insect based on the nuclear ribosomal molecular evidence. In the approach, the 18S rDNA of this insect was extracted, amplified, sequenced, and aligned, and the resultant data were used to reconstruct and analyze the phylogeny of this insect based on the catalogued data.